Building smart communities for sustainable development: Community tourism in Treasure Beach Jamaica. (7th May 2020) - McNaughton, Maurice; Rao, Lila; Verma, Sameer
Abstract : Purpose: Tourism is an important economic activity, and a significant contributor to employment, growth and sustainable development for most of the predominantly small island developing states of the Caribbean. Community-based tourism, given its intuitively natural alignment with the interests and greater inclusiveness of local actors and communities, is considered to be an important contributor to sustainable tourism. This study aims to evaluate the potential for digital technologies to amplify the distinctiveness, enhance service delivery and ultimately contribute to the sustainability of community tourism contexts. Design/methodology/approach: The research uses a form of participatory action research that involves active collaboration between researchers and practitioners. The authors propose a framework approach for implementing smart community initiatives within a community tourism context. Findings: The human-centered, participatory framework approach described in this research can help to empower community tourism by providing increased visibility and enhanced service delivery for small operators. These outcomes can become important contributions to enhancing inclusive and sustainable development and capacity for participatory, integrated and sustainable local communities – a key outcome for sustainable development goal 11 – sustainable cities and communities. Research limitations/implications: The research is ongoing with the value outcomes still emerging. The empirical domain is confined to a single geographical context, so the findings and insights may not be generalizable. Practical implications: Beyond the emerging research insights, the project produced specific digital artifacts such as geospatial data and technology platforms; and process outcomes such as training, capacity-building and empowerment of community members. In particular, youth trained to create and maintain the digital infrastructure (community mapping) provide an important local capability that can be re-purposed for other types of field-based data collection activities, thus providing alternative economic opportunities. Originality/value: The map-based information and digital content are localized to a specific geographical context, using data mapped by local actors, who possess the best local knowledge about what the community has to offer. The approach and supporting technologies can be readily replicated into other communities.